Assessing Monetary Policy Effects on Capital Markets: Evidence from the Euro Area - Teryan, Diana («Տնտեսագետ» հրատ․)
The focus of the paper is the influence the European Central Bank’s monetary policy has on the European capital market. The aim of this research is to investigate the relationship between monetary policy indicators and different segments of the capital market in the Euro area, particularly government, corporate bond and stock markets. We have used a standard structural vector autoregressive (SVAR) modelling methodology based on monthly dataset to evaluate the interrelations between observed six European variables. Impulse response functions and variance decomposition analysis have contributed to the model interpretation. Based on our estimations, we can conclude that each of the observed sectors of the European capital market is interrelated with ECB monetary indicators. The interest rate positive impulses’ impact on bond and stock markets’ volatility evolved mainly within a short period of time. Government, corporate and stock markets, in general, reacted positively to tight monetary policy, although each segment had its own behaviour throughout projection horizon. The outcome of variance decomposition analysis revealed that the fluctuations of the variables could more widely be explained by the shocks directed to themselves.
Keywords: Finance